(untitled) (American Journal of Islam and Society, 1996)
Any study of authority will need to consider the subject from a number of different perspectives, including an analysis of concepts and how bese are formulated, and a study of the effects of these concepts at both the practical and theoretical levels. The study that ensues does not claim to be the last word on the subject. Rather, its purpose is to open the door to further examination and inquiry and to critically analyze the main concept, in addition to the network of concepts attached to and contingent upon it. I shall not spend a great deal of time analyzing the lexical aspects of the concepts we are about to study, because terms and concepts are two different things. In a study of terminology, it might suffice to identify the lexical root and its particular meanings and then move on to a discussion of the usages appropriate to a particular field, subject, or science. Thereafter, one might attempt to define the term in a way that gives a clear idea of its intended meaning. A concept, however, may be described as a term connected to a network of philosophical and culhual roots. Furthermore, regardless of the diversity of its roots, a concept will always correlate with the epistemological paradigm in which it functions. Certainly this assumption holds true in regard to Islamic concepts or those concepts that are key to an understanding of the Islamic order. Surrounding the Islamic concept of divine authority, for example, there is an entire network of related concepts. Unless these related concepts are understood, both on their own and within the larger context of the Islamic order itself, the concept of divine authority will remain unclear. This network includes, for example, the concepts of divinity, creation, worship, the world and the hereafter, the divine discourse, the lawful and the unlawful, the classification of texts as relative or unqualified or ...